Community-Based Efforts to Reduce Violence: A Scoping Review on the Implementation of Cure Violence - Sara Solomon MPH, RD; Caterina G. Roman PhD; Melissa Davey-Rothwell PhD, MPH; Ruth Abaya MD, MPH; Daniel Webster ScD, MPH; Shannon Frattorolli PhD, MPH (Inquiry: The Journal of Health Care Organization, Provision, and Financing, 2025)
This scoping review aimed to identify implementation determinants, strategies, mechanisms, and outcomes of Cure Violence (CV) programs to develop an Implementation Research Logic Model (IRLM) and integrate Implementation Science (IS) principles into community violence intervention research and practice. Following Mak and Thomas methodology, we conducted a comprehensive literature search across multiple databases, including peer-reviewed articles and grey literature from 2008 to 2023. Data extraction focused on implementation constructs, study characteristics, and CV intervention details. Thematic analysis was used to synthesize findings and develop the IRLM. The review included 29 publications covering 19 distinct CV programs, primarily in the United States. While 62% of studies incorporated IS elements, only one explicitly mentioned using an IS framework. We identified 42 implementation strategies across 6 categories: hiring and retention, training, violence interruption and detection, identifying and treating high-risk individuals, changing community norms, and general implementation and sustainability. Key contextual determinants influencing implementation included funding stability, community trust, and staff characteristics. The adapted IRLM visually depicts the relationships between implementation strategies, mechanisms, and outcomes. This review highlights the need for greater integration of IS principles in CV research and practice. The proposed IRLM provides a framework for practitioners to guide implementation and for researchers to design more rigorous studies unpacking the layers of implementation, including strategies, mechanisms, and outcomes that contribute to the variation in the effectiveness of CV across different contexts. Future research should focus on testing specific implementation strategies and measuring a broader range of implementation outcomes beyond fidelity.